Ab Initio Study of Optoelectronic and Magnetic Properties of Ternary Chromium Chalcogenides - Marc Ong; Mahmoud Hammouri; Radi A. Jishi (Advances in Materials Science and Engineering)
Using first-principles calculations, we investigate the magnetic order in the ground state of several ternary chromium chalcogenide compounds. Electronic band structure calculations indicate that these compounds are either metallic or semiconductors with relatively low bandgap energies. The large optical absorption coefficients, predicted by our calculations, suggest that some of these compounds may be useful as light harvesters in solar cells or as infrared detectors.